Analisis Pengetahuan Investasi, Return Investasi dan Motivasi Investasi Terhadap Minat Investasi Mahasiswa Akuntansi Kota Batam - Elvi Felisiah; Erni Yanti Natalia (Komunitas Dosen Indonesia, 2023)
Investment is a preparatory action carried out by someone to prepare funds in the future. This preparation is done by investing, such as saving in the capital market, managing money to turn into a business, or buying property. In addition, by investing, the community has participated in building the country's economic development, this happens because with investment, the money circulating in the market can be monitored by the government. Investments can be made by all groups, especially students, right now everything become easier especially the requirement for starting an investment, many of securities investment only need IDR 100,000 to start an investment. The main purpose for doing this research is to know what kind of influence that come from effect knowledge of investment, investment returns and motivation of investment on the investment interest of accounting students in Batam City. The source of data used for research is using primari data, namely by distributing questionnaires to accounting students at Batam International University. The population used in this study was 609 students and then calculated using slovin technic with 5% margin of error. The application used to process questionnaire data is SPSS V26. The results of this research shown that knowledge of investment, investment returns and investment motivatiion have a significant effect on the investment interest of accountning students based in Batam City.